2012
DOI: 10.1007/978-1-61779-953-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gold Nanoparticle Conjugation on the Activity and Stability of Functional Proteins

Abstract: Immobilization of functional proteins such as enzymes on solid surfaces produces a variety of effects ranging from the reversal and strong inhibition to the enhancement of protein stability and function. Such effects are protein-dependent and are affected by the physical and chemical properties of the surfaces. Functional consequences of protein immobilization on the surface of gold nanoparticles (AuNPs) are protein-dependent and require thorough investigation using suitable functional tests. However, traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…When compared to the reference recipe [12], the ligand/Au ratio was changed from 3 to 9 in order to obtain smaller AuNPs. e.g., bovine catalase [7], show a higher stability in harsh conditions in presence of AuNPs. On the other hand, when Aβ peptide, the amyloidogenic fragment from Amyloid Precursor Protein (APP), whose fibril deposition has been related to Alzheimer's disease onset [8], was incubated with different nanoparticles (NPs), various effects on fibrillogenesis were observed.…”
Section: Aunp Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the reference recipe [12], the ligand/Au ratio was changed from 3 to 9 in order to obtain smaller AuNPs. e.g., bovine catalase [7], show a higher stability in harsh conditions in presence of AuNPs. On the other hand, when Aβ peptide, the amyloidogenic fragment from Amyloid Precursor Protein (APP), whose fibril deposition has been related to Alzheimer's disease onset [8], was incubated with different nanoparticles (NPs), various effects on fibrillogenesis were observed.…”
Section: Aunp Synthesis and Characterizationmentioning
confidence: 99%
“…However, the challenging investigation of protein-nanomaterial interface also proved so intriguing that no general trends could be drawn so far. For example, it has been reported that some enzymes, e.g., lysozyme, chymotrypsin, and fibrinogen [4,5], lose their catalytic activity upon interacting with gold nanoparticles (AuNPs), other ones, e.g., pepsin [6], retain their functionality and some other ones, e.g., bovine catalase [7], show a higher stability in harsh conditions in presence of AuNPs. On the other hand, when Aβ peptide, the amyloidogenic fragment from Amyloid Precursor Protein (APP), whose fibril deposition has been related to Alzheimer's disease onset [8], was incubated with different nanoparticles (NPs), various effects on fibrillogenesis were observed.…”
Section: Introductionmentioning
confidence: 99%
“…-conformation changes → blocked or enhanced presentation of active sites and subsequent functional changes [21,22] -conferring a biological identity -altered interaction/uptake and biodistribution [23][24][25] -altered propensity for protein-protein interactions (e.g., fibrillation) [26] -altered surface characteristics and thereby stability and dispersability [8,27] and potentially also dissolution potential (as per environmental macromolecules such as humic acids) although limited literature [28] -oxidative effects -lesions, post-translational effects, etc. [29].…”
Section: Effect Of Adsorption On Biomoleculesmentioning
confidence: 99%
“… 3 The above toxicity of soluble Au 3+ is attributed to its selective binding ability toward DNA 4 and enzymes. 5 Au 3+ is responsible for enzyme depletion and protein denaturation against selective cellular targets and lysosomal dysfunction, which subsequently results in DNA and membrane damage. 6 Au 3+ also promotes the oxidative DNA damage by catalyzing the free-radical generation of various chemical entities frequently used in biochemical and biological studies.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the Au cations, especially Au 3+ , are reported to be toxic toward human and aquatic species . The above toxicity of soluble Au 3+ is attributed to its selective binding ability toward DNA and enzymes . Au 3+ is responsible for enzyme depletion and protein denaturation against selective cellular targets and lysosomal dysfunction, which subsequently results in DNA and membrane damage .…”
Section: Introductionmentioning
confidence: 99%